Identification of OCA2 as a novel locus for the co‐morbidity of asthma‐plus‐eczema. Issue 1 (3rd July 2021) - Margaritte‐Jeannin, Patricia; Budu‐Aggrey, Ashley; Ege, Markus; Madore, Anne‐Marie; Linhard, Christophe; Mohamdi, Hamida; von Mutius, Erika; Granell, Raquel; Demenais, Florence; Laprise, Catherine; Bouzigon, Emmanuelle; Dizier, Marie‐Hélène
Abstract: Background: Numerous genes have been associated with the three most common allergic diseases (asthma, allergic rhinitis or eczema) but these genes explain only a part of the heritability. In the vast majority of genetic studies, complex phenotypes such as co‐morbidity of two of these diseases, have not been considered. This may partly explain missing heritability. Objective: To identify genetic variants specifically associated with the co‐morbidity of asthma‐plus‐eczema. Methods: We first conducted a meta‐analysis of four GWAS (Genome‐Wide Association Study) of the combined asthma‐plus‐eczema phenotype (total of 8807 European‐ancestry subjects of whom 1208 subjects had both asthma and eczema). To assess whether the association with SNP(s) was specific to the co‐morbidity, we also conducted a meta‐analysis of homogeneity test of association according to disease status ("asthma‐plus‐eczema" vs. the presence of only one disease "asthma only or eczema only"). We then used a joint test by combining the two test statistics from the co‐morbidity‐SNP association and the phenotypic heterogeneity of SNP effect meta‐analyses. Results: Seven SNPs were detected for specific association to the asthma‐plus‐eczema co‐morbidity, two with significant and five with suggestive evidence using the joint test after correction for multiple testing. The two significant SNPs are located in the OCA2 gene (Oculocutaneous Albinism II), a new locus never detected for significant evidence of association with any allergic disease. This gene is a promising candidate gene, because of its link to skin and lung diseases, and to epithelial barrier and immune mechanisms. Conclusion: Our study underlines the importance of studying sub‐phenotypes as co‐morbidities to detect new susceptibility genes. Abstract : A meta‐analysis of four GWAS among population and family based samples to identify new susceptibility genes for the co‐morbidity of asthma‐plus‐eczema. Identification of OCA2, a new gene associated specifically with the phenotype of asthma‐plus‐eczema. The candidate gene OCA2 is linked to skin and lung diseases, epithelial barrier and immunology.